EFL secondary teachers’ assessment literacy: Assessment conceptions and practices - Roghibatul Luthfiyyah; Iin Wariin Basyari; Dwiniasih Dwiniasih (Journal on English as a Foreign Language, 2020)
Assessment literacy is defined as knowledge, conceptions, and skills to conduct an assessment. Having sufficient assessment literacy levels, teachers can assist students in improving learning and in achieving learning outcomes. This study employs a descriptive quantitative design that explores EFL secondary teachers' assessment literacy and assessment practice. The data were gathered using an online survey and semi-structured interviews. Forty-eight respondents willingly fulfilled an online questionnaire containing 32 questions adapted from the Teachers Assessment Literacy Questionnaire (TALQ). The data obtained from the survey were analyzed using descriptive statistics. Furthermore, three participants representing each assessment literacy level were selected for interviews to explore their classroom assessment practice. The interview data were analyzed using thematic analysis in terms of the conceptions of assessment, the procedure of assessment construction, and some challenges in assessment practice. The findings reveal that EFL secondary teachers generally have a moderate assessment literacy level. However, the participants reflect different conceptions of assessment, procedures, and challenges in assessment practice depending on an individual level of assessment literacy, institutional and national policies, and socio-culture factors. It shows that assessment literacy is not a single element that can influence teachers' assessment practices.